Bragg coherent imaging of nanoprecipitates: role of superstructure reflections. Issue 5 (29th September 2020) - Dupraz, Maxime; Leake, Steven J.; Richard, Marie-Ingrid
Abstract : Detailed numerical simulations are presented, aimed at demonstrating the relevance of Bragg coherent diffraction imaging for elucidating coherent nanoprecipitates and more generally chemically ordered phases Abstract : Coherent precipitation of ordered phases is responsible for providing exceptional high‐temperature mechanical properties in a wide range of compositionally complex alloys. Ordered phases are also essential to enhance the magnetic or catalytic properties of alloyed nanoparticles. The present work aims to demonstrate the relevance of Bragg coherent diffraction imaging (BCDI) for studying bulk and thin‐film samples or isolated nanoparticles containing coherent nanoprecipitates/ordered phases. The structures of crystals of a few tens of nanometres in size are modelled with realistic interatomic potentials and are relaxed after introduction of coherent ordered nanoprecipitates. Diffraction patterns from fundamental and superstructure reflections are calculated in the kinematic approximation and used as input to retrieve the strain fields using algorithmic inversion. First, the case of single nanoprecipitates is tackled and it is shown that the strain field distribution from the ordered phase is retrieved very accurately. Then, the influence of the order parameter S on the strain field retrieved from the superstructure reflections is investigated. A very accurate strain distribution can be retrieved for partially ordered phases with large and inhomogeneous strains. Subsequently, the relevance of BCDI is evaluated for the study of systems containing many precipitates, and it is demonstrated that the technique is relevant for such systems. Finally, the experimental feasibility of using BCDI to image ordered phases is discussed in the light of the new possibilities offered by fourth‐generation synchrotron sources.